A case for Planetary Health/GeoHealth. Issue 2 (20th April 2017) - Almada, Amalia A.; Golden, Christopher D.; Osofsky, Steven A.; Myers, Samuel S.
Abstract: Concern has been spreading across scientific disciplines that the pervasive human transformation of Earth's natural systems is an urgent threat to human health. The simultaneous emergence of "GeoHealth" and "Planetary Health" signals recognition that developing a new relationship between humanity and our natural systems is becoming an urgent global health priority—if we are to prevent a backsliding from the past century's great public health gains. Achieving meaningful progress will require collaboration across a broad swath of scientific disciplines as well as with policy makers, natural resource managers, members of faith communities, and movement builders around the world in order to build a rigorous evidence base of scientific understanding as the foundation for more robust policy and resource management decisions that incorporate both environmental and human health outcomes. Key Points: Global environmental change is an urgent threat to human health Action‐focused, transdisciplinary research to optimize the health of people and ecosystems is needed The emerging field of Planetary Health/GeoHealth aims to build a scientific evidence base to support more robust policy decisions